Limitations of ethical trading: a case study of the avocado market in North America - Paola Pérez Yee Palacios (Trans-pasando Fronteras)
The global avocado market has proliferated due to increased demand, especially in North America. However, this surge in avocado trade has led to significant environmental concerns, particularly habitat loss. Large-scale avocado farming is associated with deforestation and the disruption of ecosystems, leading to the degradation of natural habitats. These issues are most evident in regions where avocado production is concentrated, such as Mexico, the leading exporter to North America. Critical ecosystems such as that of the Oyamel forest, home of the Monarch butterfly in its overwinter phase, are being negatively altered to meet demand. As the avocado trade continues to expand, ethical trading practices have emerged as a vital means of balancing economic benefits with sustainable farming methods. This approach is crucial for mitigating further environmental damage and preserving biodiversity. However, it is essential to critically analyze the limitations of ethical trading, particularly regarding the standards that govern its implementation.